2020
DOI: 10.21203/rs.3.rs-34034/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of Preventive, Supportive and Awareness Building Measures among International Students in China in Response to COVID-19: A Structural Equation Modeling Approach

Abstract: Background The Coronavirus Disease 2019 (COVID-19) with its high mortality, stigma and panic has compelled many cities and countries to complete lockdown. The worldwide student group is one of the most affected and vulnerable communities in this situation. Our current study aimed to assess the impact of the behavior change communication among international students in China in current COVID-19 crisis.Methods In this paper, we have utilized partial least squares-structural equation modeling (PLS-SEM) to underst… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The internal construction of the framework revealed that social aspects have the most substantial impact on Quality of Life (0.446), followed by Psychological Aspects (0.329), Environmental aspects (0.198) and Physical Aspects (0.237). These outcomes indicate the structural path of all the hypothesized constructs contains signi cant correlational impacts, which is well above the expected values of 0.2[28, 29,33]. Since, the relationship between environmental aspects and quality of life (QOL) is very close to the expected value and well passed the threshold value of 0.1, therefore, in the context of the study, we assumed it passed the signi cance test as suggested [32,34].…”
Section: Pls-sem Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The internal construction of the framework revealed that social aspects have the most substantial impact on Quality of Life (0.446), followed by Psychological Aspects (0.329), Environmental aspects (0.198) and Physical Aspects (0.237). These outcomes indicate the structural path of all the hypothesized constructs contains signi cant correlational impacts, which is well above the expected values of 0.2[28, 29,33]. Since, the relationship between environmental aspects and quality of life (QOL) is very close to the expected value and well passed the threshold value of 0.1, therefore, in the context of the study, we assumed it passed the signi cance test as suggested [32,34].…”
Section: Pls-sem Resultsmentioning
confidence: 91%
“…Structural equation modeling (SEM) is designed with the two-phase model (i) measurement model and (ii) structural model. The measurement model depicts the inner relationships between latent variables and observed variables, and the latter, along with the structural model, is used to investigate loadings and estimate indicators [27][28][29]. The conceptual framework model was run using Smart PLS 2.0, and the structural framework used in the hypothesis testing segment is shown in Fig.…”
Section: Assessing the Pls-sem Algorithms Modelmentioning
confidence: 99%